AKURASI DATA PENGUKURAN TINGGI MENGGUNAKAN 3D OBJEK TRACKING BERBASIS AUGMENTED REALITY - Mandarani, Putri; Azha, Rifo Dwipa; Hamdi, Yori; Swara, Ganda Yoga; Anisya, Anisya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The height of an object is required for data on making driver's licenses, entering game rides, applying for jobs, for health and so on. Measuring the height of an object often finds problems with the accuracy of calculations expressed in the form of numbers. The limited ability of the tool and the inability of humans to read the measuring results correctly, become factors in the inaccuracy of the measurement results of an object. To solve these problems, an application was created that can produce data accurately and easily in measurement. The object height measurement application is designed and built using Augmented Reality with markerless based tracking method. The tests carried out are blackbox testing and data accuracy. The results show that functionally, the application runs well and objects are detected appropriately. The accuracy rate of measuring the height of objects at a distance of 1 meter is 96%; the distance of 1.5 meters is 98%; The distance of 2 meters is 97%, and at a distance of 2.5 meters it is 97%. It can be said that in bright light conditions with a lux of 1000, measurements using this application can work well at a distance of 1.5 meters. This result can be used as a reference for users of other AR-based object height measurement applications in positioning the distance of objects and cameras used, thus helping users get height data of an object easily and accurately.Keywords: Accuracy, Augmented Reality, height, markerless, 3D object tracking